Laboratory monitoring of bacterial gastroenteric pathogens Salmonella and Shigella in Shanghai, China 2006–2012. (15th May 2014) - ZHANG, J.; WANG, F.; JIN, H.; HU, J.; YUAN, Z.; SHI, W.; YANG, X.; MENG, J.; XU, X.
SUMMARY: In 2006 we initiated an enhanced laboratory-based surveillance of Salmonella and Shigella infections in Shanghai, China. A total of 4483 Salmonella and 2226 Shigella isolates were recovered from stool specimens by 2012. In 80 identified Salmonella serovars, Enteritidis (34·5%) and Typhimurium (26·2%) were the most common. Shigella ( S. ) sonnei accounted for 63·9% of human Shigella infections over the same time period, and replaced S. flexneri to become the primary cause of shigellosis since 2010. Overall, a high level of antimicrobial resistance was observed in Salmonella and Shigella, particularly to nalidixic acid, ampicillin, and tetracycline. Ciprofloxacin resistance was common in Salmonella Typhimurium (21·0%) and S. flexneri (37·6%). The cephalosporin resistance in both pathogens also increased over the years, ranging from 3·4% to 7·0% in Salmonella, and from 10·4% to 28·6% in Shigella . Resistance to multiple antimicrobials was also identified in a large number of the isolates. This study provides insight into the distribution of Salmonella and Shigella in diarrhoeal diseases.